EXPERIMENTAL VERIFICATION OF THE ADEQUACY OF THE ANALYTICAL MODEL OF GRAVITATIONAL GRAIN MOVEMENT IN A SCREW CHANNEL WITH TWO VARIABLE ANGLES - Antonets, A.; Flegantov, L.; Arendarenko, V.; Ivanov, O.; Yaprynets, T. (Scientific Progress & Innovations, 2022)
The problem of injuring the grain during its loading into the silo remains relevant. One of the ways to solve it is to ensure controlled gravitational movement of grain in a spiral with acceleration and braking areas. The analytical model, which is suggested, makes it possible to determine the speed of grain flow at any time, both on the acceleration and the braking part of the screw channel. The model also takes into account the dependency between the angles α and β of the acceleration and braking areas. Based on the theoretical model, a technical description of the peripheral open screw channel (POSC) is proposed. The channel has acceleration and braking areas with discretely variable descent angles. A suitable laboratory sample for experimental research was built on this basis. The first stage of the research defined the nature of the change in the braking area angle β from the change in the acceleration area angle α. The influence of the initial grain height h о and the radius r of the channel spiral on these dependencies is shown. In the second stage, the final speed of winter wheat with 14% moisture was investigated by varying the angles of the acceleration and braking areas and holding other parameters constant. The ratio that determines the relationship between the angles was maintained. Five parallel experiments were planned to obtain reliable data in each combination of variables with a significance level of 5 %. The statistical analysis included checking the homogeneity of variances of Cochran's experiments, checking the normal distribution of the residual series by the RS criterion, finding the relative error of residues and their statistical estimates and determining the multiple correlation coefficient. The analysis showed the adequacy and acceptable accuracy of the proposed analytical model. The difference between the obtained results does not exceed 10 %. The results of the experimental and theoretical studies made it possible to establish relationships between key parameters of POSC, in particular, the recommended angles of 41° ... 45° for acceleration and 39° ... 35° for braking areas, respectively, and a h/r ratio of at least 0.6 ... 0.7 are justified.